From modernity to memorial: the changing meanings of the 1930s cinema in Nottingham - Stubbings, Sarah (2004)
This work examines local press reporting of the 1930s cinema from 1930 up to the present day. By focusing on one particular city, Nottingham, I formulate an analysis of the place that cinema has occupied in the city's history. Utilising the local press as the primary source enables me to situate the discourses on the cinema building and the practice of cinema-going within the broader socio-cultural contexts and history of the city. The work incorporates all the different forms of local press coverage of cinema: editorials, advertising, news, features and letters. It argues that the meanings of the 1930s cinema alter significantly over time with regard to changing perceptions of the city and the suburb, of modernity and tradition, of the value ascribed to cinema architecture, and the significance attached to popular memory. It also demonstrates that the meanings of the 1930s cinema are defined by the different agendas of particular groups, and that the local press is significant in determining which of these agendas are prioritised and portrayed as representing the consensus.